2019
DOI: 10.1002/ijgo.12929
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery among nulliparous women with single, cephalic, term pregnancies: The WHO global survey on maternal and perinatal health, 2004–2008

Abstract: Objective:To determine risk factors associated with cesarean delivery among nulliparous women in spontaneous labor with a single, cephalic, term pregnancy (Robson group 1). Methods: Data were assessed from the WHO Global Survey of Maternal and PerinatalHealth conducted in 2004-2008. Results: Among 82 280 women in Robson group 1, 67 698 (82.3%) had vaginal and 14 578 (17.7%) had cesarean delivery. In adjusted analyses, maternal factors associated with cesarean included age older than 18 years, being overweig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
2
5
0
1
Order By: Relevance
“…We found a monotonic correlation between maternal BMI and risk of intrapartum cesarean section, with the highest risk associated with obesity classes II and III. These findings are consistent with previous studies describing the association between maternal obesity and increased risk of intrapartum cesarean section 6,18,19 . This study demonstrates an elevated risk of intrapartum cesarean section associated with maternal obesity, even for women in TGCS group 1.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found a monotonic correlation between maternal BMI and risk of intrapartum cesarean section, with the highest risk associated with obesity classes II and III. These findings are consistent with previous studies describing the association between maternal obesity and increased risk of intrapartum cesarean section 6,18,19 . This study demonstrates an elevated risk of intrapartum cesarean section associated with maternal obesity, even for women in TGCS group 1.…”
Section: Discussionsupporting
confidence: 93%
“…This study demonstrates an elevated risk of intrapartum cesarean section associated with maternal obesity, even for women in TGCS group 1. This is consistent with Harrison et al, who found that overweight and obese women in TGCS group 1 had a significantly higher incidence of intrapartum cesarean section 19 . Note that even though we found a borderline statistically significant reduced risk of intrapartum cesarean section among underweight women, this should be interpreted with caution, as the number of cases among underweight women was small.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Robson Groups 2 and 4 have a higher primary cesarean birth rate (31.0%) than that of Robson Groups 1 and 3 (17.6%, data no shown), the latter of which are known to contribute most significantly to primary cesarean birth rates, globally [ 3 ]. The difference between Groups 2 and 4 versus Groups 1 and 3 is that the former goes into labor spontaneously and delivers without augmentation and the latter requires induction, augmentation, or was delivered by cesarean before the onset of labor.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization recommends applying the Robson classification for cesarean birth to birth cohorts to better understand which of ten mutually exclusive subgroups are contributing to cesarean birth rates [ 1 , 2 ]. Analyses generally focus on nulliparous (Group 1) and multiparous (Group 3) women with single, cephalic, term fetuses in spontaneous labor because these women usually account for the greatest proportion of women delivering in any given cohort and can contribute to preventable primary cesarean birth rates [ 3 ]. When we applied the Robson classification to a convenience sample of women undergoing cesarean birth at our study site, we found that cesarean birth rates were relatively low in these subgroups (19.4% and 16.1%, respectively, though they accounted for the most cesarean births at the site) [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%